Ակների վանական միաբանությունը և գրատան ժառանգությունը (ԺԳ-ԺԴ դարեր) - Բադալյան, Հասմիկ
The article is devoted to the nearly 130-year history of Akner Monastery, one of the spiritual and cultural centers of Cilician Armenia, to the activities of monastic scribes and to the appraisal of the scriptorium’s heritage. The study is based on fifteen handwritten sources of Mashtots Matenadaran, twenty-five catalogues of Armenian manuscripts kept in different depositories, as well as on well-known or newly discovered data in historical and philological studies. For the first time, the names of twenty-six scribes of Akner, instead of sixteen known so far, nine miniaturists, five musicians, more or less prominent ministers of the monastery and the scope of their activities, as well as the biographical information about the scribes and the circumstances in which they copied manuscripts have been assessed and precised. The study reveals the overall picture of the cultural processes in the 13th-14th centuries, when the Akner Congregation became known in Cilicia and throughout Armenia as a scriptorium, a center of calligraphy, painting, music, and book-binding. The monastery maintained close ties with the cultural centers of Cilicia and Eastern Armenia (Sis, Ark‘akaghin, Avag, Skewṛa, Khṛchka, Bjni, and Gladzor). The article also contains a list of the scribes, musicians and painters of the monastery, together with their works. Статья посвящена почти 130-летней истории монастыря Акнер, одного из духовно-культурных центров Киликийской Армении, деятельности монастырских писцов и оценке наследия скриптория. Исследование основано на пятнадцати рукописных источниках Матенадарана имени Маштоца, 25-и ка- талогах армянских рукописей, а также на результатах историко-филологиче- ских исследований. Впервые были уточнены, дополнены и введены в научный оборот имена 26-и акнерских писцов (в то время как ранее были известны 16), девяти ми- ниатюристов и пяти музыкантов, более и менее значительных служителей монастыря, результаты их деятельности, а также были уточнены и выяснены биографические данные акнерских писцов и обстоятельства переписки ими рукописей. Исследование раскрывает общую картину культурных процессов того времени. В XIII-XIV веках конгрегация Акнера стала известна в Киликии и во всей Армении как центр каллиграфии, миниатюры, музыки и переплетного дела. Монастырь поддерживал тесные связи с культурными центрами Киликии и Восточной Армении (Сис, Аркакагин, Аваг, Скевра, Хочка, Бджни, Гладзор). В статье представлен также список писцов, музыкантов и художников монастыря, наряду с их трудами.
Keywords: Բանասիրություն; Գրչության կենտրոն